Study of maternal profile in children admitted to nutritional rehabilitation centre at a tertiary hospital - B. M., Nagabhushan; J., Poornima; R., Premalatha (International Journal of Contemporary Pediatrics, 2017)
Background: Study of maternal profile in children affected with severe acute malnutrition is very essential. Maternal nutritional status, social and educational status and her medical conditions have direct impact on malnutrition of children. Small efforts to study the maternal profile for one year in our nutritional rehabilitation centre. Methods: A one-year prospective study was carried out in a nutritional rehabilitation centre, Department of paediatrics, Bangalore Medical College and Research Institute, Bangalore, Karnataka, India, from September 2015 to August 2016. All maternal details were recorded. All mothers were examined for height weight BMI, checked for vitals and underlying medical conditions. Anaemia is confirmed by laboratory test. Results: Out of 302 mothers enrolled for study, majority were 23 plus or minus 5 years aged mothers. More than 33.7% mothers were under weight. Around 8% mothers were pre-obese and obese. Nearly 88% mothers were found to have anemia, 39% mothers had mild anemia, 30% had moderate anemia, 30% had severe anemia. Hypertension, hypothyroidism, tuberculosis and gynecological problems were other major medical illness seen in these mothers. Majority of the mothers were primigravida (42.38%), around 22% mothers were having birth order more than 3 children. Nearly 78% mothers were not practicing any family planning, only 21% mothers were aware and practicing family planning. Nearly 45% mothers were educated less than high school education. Only few mothers (18%) have studied till post-graduation. Conclusions: In the study majority of the mothers were found to be under weight, nearly 88% mother had anaemia, several underlying medical conditions were detected in mothers, most of the mothers were not practicing family planning, majority of the mothers were studied below high school education.